STUDI PENERAPAN HACCP PADA PRODUSEN MI GLOSOR DI KOTA BOGOR - Jumiono, Aji; Dihansih, Elis; Rochmana, Iwan (Jurnal Pertanian, 2020)
This study aims to examine the application of HACCP in the glossy noodle (mi glosor) home industry in CV Taruna located in Bogor City by analyzing the stages of work activities in glossy noodle producers. Evaluation of the application of HACCP was carried out using standards recommended by the National Standards Agency (BSN) in 1999. This study began by analyzing the application of Good Processed Food Production Methods (CPPB) that were applied at CV Taruna. The application of CP Taruna CV Taruna is at level 4 which is the basic assessment in improving the application of HACCP in this small business. The next step is to analyze the flow diagram of the process of making glossy noodles and the determination of critical control points, critical limits, monitoring and preventive measures. There are 8 critical control points in the process of making glossy noodles. In the final stage, documentation and monitoring are made to control the implementation of the HACCP system that is run. The results of this study provide several recommendations for improving the application of HACCP in the process of producing glossy noodles at CV Taruna to improve its food safety application program.